Agrarian Economics at Vilnius Research Institutes in the Years 1945-1990 - Poviliūnas, Antanas (Ekonomika, 2000)
During the years 1945-1990 the centers of agrarian economics science were formed in Kaunas and Vilnius. The Institute of Economics at the Academy of Science and the Institute of Agricultural Economics at the Ministry of Agriculture have functioned in Vilnius. The main trends of their’s research were alii following: economic estimation of natural resources, estimation of agricultural production potential and usage, equalization of economic opportunities in farming, distribution and specialization of agriculture.